FUTURE FIELD SERVICE BUSINESS OPERATIONS ENHANCEMENT USING AI AND ROBOTS - Kiran Nagubandi, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This article explores the transformative impact of artificial intelligence (AI) and robotics on the field service management (FSM) industry. It examines how these technologies are reshaping business processes and operations in field service, focusing on key areas such as predictive maintenance, robotic automation, workforce management, and customer interaction. The paper discusses AI-driven predictive maintenance using IoT sensors and machine learning algorithms, the role of robots in inspections and repairs, AI-enhanced workforce management for optimized scheduling and skill matching, and improved customer support through AI-powered systems. Additionally, it addresses the challenges of technical complexity, workforce adaptation, and data security, alongside opportunities for increased efficiency, improved accuracy, and enhanced customer satisfaction. Case studies of Siemens and Boston Dynamics illustrate real-world applications of these technologies in FSM. The article concludes by emphasizing the crucial role of AI and robotics in shaping the future of field service management, highlighting the need for organizations to navigate implementation challenges effectively to lead in this evolving industry landscape.